2021
DOI: 10.3389/feart.2021.641416
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Fault Valve Behavior in a Continental Collision Area: Evidence From Tilt/Strain Measurements in Northern Adria

Abstract: We analyzed the data recorded by the NE-Italy subsurface tilt and strainmeter network evidencing a coherent transient signal in the recordings of four tiltmeter sites in the 1984–1990 period that produced a tilt along the main fractures. Borrowing from classical seismology techniques, we used the uprise times to locate the transient signal source. The propagation velocity is compatible with a fluid diffusion process that starts from a source located close to the hypocenter of the February 10, 1983 Uccea earthq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Various experiments indicated that fluid pressure mainly induces aseismic deformation that triggers seismicity through stress perturbations on fault asperities with appropriate background stresses and frictional instability conditions (De Barros et al, 2020). The alternating bursts of seismicity and quiescence observed in some swarms can be explained by the fault-valve model (Sibson, 1992;Rossi et al, 2021). According to Hainzl (2004), at smaller Dh the intervals between subclusters become longer and the total duration of activity increases.…”
Section: Fluid Diffusionmentioning
confidence: 99%
“…Various experiments indicated that fluid pressure mainly induces aseismic deformation that triggers seismicity through stress perturbations on fault asperities with appropriate background stresses and frictional instability conditions (De Barros et al, 2020). The alternating bursts of seismicity and quiescence observed in some swarms can be explained by the fault-valve model (Sibson, 1992;Rossi et al, 2021). According to Hainzl (2004), at smaller Dh the intervals between subclusters become longer and the total duration of activity increases.…”
Section: Fluid Diffusionmentioning
confidence: 99%
“…Several other studies used geodetic observations, focusing on non-tectonic processes affecting the study area. Rossi et al [57][58][59] described transient deformation signals associated with pore pressure variations in rocks in response to tectonic stress. Stocchi et al [60] estimated the post-glacial isostatic rebound along the Alpine belt as ~1/3 of the measured vertical rates.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies focused on the definition of the geometrical and kinematic behaviors of the active faults and their seismogenic potential (e.g., D'Agostino et al, 2005;Bechtold et al, 2009;Cheloni et al, 2014;Moulin et al, 2016;Serpelloni et al, 2016;Anderlini et al, 2020). Rossi et al (2016Rossi et al ( , 2018Rossi et al ( , 2021 have evidenced transient deformations propagating in the region and interpreted them due to pore pressure variations in response to the tectonic stresses.…”
Section: Introductionmentioning
confidence: 99%